To Determine the Diagnostic Accuracy of Magnetic Resonance Spectroscopy (MRS) In Detection of Prostate Cancer in Patients with Prostatomegaly and Elevated PSA Levels, Taking Biopsy as Gold Standard - Gul, Dr. Rafay; Pathan, Dr. Hina; Darira, Dr. Jaideep; Shazlee, Dr. Kashif; Amir Ali, Dr. Ashraf; Zafar, Dr. Sara (International Journal of Innovative Research in Medical Science, 2022)
Objective: To determine the diagnostic accuracy of magnetic resonance spectroscopy(MRS) in detection of prostatic cancer in patients with prostatomegaly and elevated PSA levels, taking biopsy as gold standard. Study Design: Cross sectional study. Duration and place of study: Department of Diagnostic Radiology, Dr. Zia Uddin University Hospital, Karachi from February 1 to August 31,2020. Methods: High risk patients for prostatic carcinoma and patients meeting inclusion criteria were referred to the radiology department of Dr, Zia Uddin hospital for MRI pelvis. Purpose and procedure of study were explained after taking an informed consent. All examinations were performed and the collected data on MR spectroscopic imaging protocol (spectra and associated metabolic ratios) was more pronounced than conventional spin echo sequences. Choline peak elevation and choline-creatinine ratios > 2 in a suspected area as compared to adjacent normal prostatic tissue was labelled as prostate cancer. This information along with the age, duration of symptoms, patient’s educational status, and weight of patient and size of lesion were collected. Results: The specificity sensitivity, positive and negative predictive value and accuracy of MRS for diagnosis of Prostate cancer was 85.40%, 78.84%, 69.64%, 90.48% and 81.22%, respectively. Conclusion: The combined effectiveness of conventional MR images along with metabolic data of MRSI will help to enhance and make presumptive diagnosis of prostate carcinoma. The implementation and standardization of MRS will definitely help in future to diagnose disease in very early stage, thus reducing the chance of morbidity and mortality to a certain level.